2008
DOI: 10.1021/ac701648p
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ion Utilization Efficiency Using an Electrodynamic Ion Funnel Trap as an Injection Mechanism for Ion Mobility Spectrometry

Abstract: Conventional ion mobility spectrometers that sample ion packets from continuous sources have traditionally been constrained by an inherently low duty cycle. As such, ion utilization efficiencies have been limited to <1% in order to maintain instrumental resolving power. Using a modified electrodynamic ion funnel, we demonstrated the ability to accumulate, store, and eject ions in conjunction with ion mobility spectrometry (IMS), which elevated the charge density of the ion packets ejected from the ion funnel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 40 publications
1
134
0
Order By: Relevance
“…The last electrode is supplied with the DC-only stopping potential and is fitted with a grid (300 lpi nickel, Precision Eforming, Cortland, NY) to improve the trapping efficiency of the device. It should be noted here that a recent high pressure ion funnel trap developed by Smith and colleagues for ion trapping and gating into an IM-MS utilizes multiple grids in its design to mitigate undesirable field penetration of the stop potential into the funnel region 34. A multiple grid design applied to the keyhole ion funnel described here is also expected to improve the overall performance in terms of charge capacity and pulse response times.…”
Section: Methodsmentioning
confidence: 99%
“…The last electrode is supplied with the DC-only stopping potential and is fitted with a grid (300 lpi nickel, Precision Eforming, Cortland, NY) to improve the trapping efficiency of the device. It should be noted here that a recent high pressure ion funnel trap developed by Smith and colleagues for ion trapping and gating into an IM-MS utilizes multiple grids in its design to mitigate undesirable field penetration of the stop potential into the funnel region 34. A multiple grid design applied to the keyhole ion funnel described here is also expected to improve the overall performance in terms of charge capacity and pulse response times.…”
Section: Methodsmentioning
confidence: 99%
“…In the present work, the entrance and exit funnel regions are pumped using a two-stage rotary vane vacuum pump (Alcatel, 2033 SD, 39 m 3 /h; Hingham, MA, USA). The magnitude of the gas velocity was determined at the position of ion elution (z = 23.3 mm, see Figure 4) using the signal at m/z 922 contained in ESI tuning mix (P 3 N 3 (OCH 3 CF 2 CF 2 ) 6 …”
Section: Instrumentationmentioning
confidence: 99%
“…In the past few decades, several advances coupling drift tube IMS and other time-dispersive methods (i.e., traveling wave IMS) to mass spectrometry (MS) [1][2][3][4][5][6][7][8][9][10] have extended its versatility for a range of chemical [11][12][13][14][15][16][17], physical [18][19][20][21][22][23], and biomolecular structural studies [24][25][26][27][28][29][30][31][32][33]. Still relatively new to the biomedical field, several groups have recently begun to incorporate LC-IMS-MS workflows in proteomics studies [34][35][36][37], and enhanced performance has been demonstrated [38].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial DESI stage can be modified and used also for other compatible ambient DI techniques, but their principles and applications are beyond the scope of this article. Efficiency of the ion transport through the atmospheric pressure inlet, a bottleneck in both DESI and conventional ESI, is currently debated in the literature (Clowers et al 2008;Kelly et al 2008;Page et al 2008;Volný and Turecek 2006).…”
Section: Metabolites and Pharmaceuticalsmentioning
confidence: 99%